Correction: Engineering strategies for rational polyketide synthase design. Issue 7 (8th July 2021) - Klaus, Maja; Grininger, Martin
Abstract : Correction for 'Engineering strategies for rational polyketide synthase design' by Maja Klaus et al., Nat. Prod. Rep., 2018, 35, 1070–1081, DOI: ; 10.1039/C8NP00030A .